Employment Formalization in Indonesia: Role of Parents’ Employment Mobility Toward Children’s Employment Mobility - Kadir Ruslan; Weni Lidya Sukma (Future Science, 2023)
This study aims to analyze the impact of parents’ employment status mobility on the children’s employment status mobility. In doing so, we applied a two-stage multinomial logistic regression model. In this research, employment status mobility refers to a mobility status from informal to formal jobs and vice versa. Using data from the Indonesian Family Life Survey (IFLS) for the period 2007 and 2014, the profile of the Indonesian workforce was dominated by stayers. The estimation results of multinomial logistic regression indicate that only fathers’ employment status mobility has a significant effect on the children’s employment status mobility, where fathers who are stayers and experiencing upward mobility will provide greater opportunities for their children to be stayers and fewer opportunities to experience downward mobility. Moreover, the employment status mobility of mothers does not have a significant impact on their children’s employment mobility. Our study points out the pivotal role of fathers in influencing employment formalization in Indonesia. Our findings could be valuable inputs for policy-making regarding employment formalization in Indonesia.